Telecommunications consumers: A behavioural economic analysis - Pete Lunn (The Economic and Social Research Institute (ESRI), 2011)
This paper argues that telecommunications markets present the consumer with a decision-making environment that is particularly likely to be prone to established biases in consumer decision-making. The analysis identifies four properties of telecommunications markets, which in combination are probably unique and which may make the sector prey to biases identified by behavioural economics. The analysis offers a range of known behavioural phenomena that, first, may help to explain the generally low levels of switching between telecommunications providers and, second, could result in failure to select optimum contracts, because of inaccurate expectations of usage or time inconsistent preferences. While more research is required to assess the merit of these hypotheses, they raise the possibility that telecommunications markets may be inefficient and prone to less effective competition than many other consumer markets. Potential policy responses are also discussed.
Keywords: 330; Telecommunications; Decision-making biases; Behavioural economics; Regulation